2022
DOI: 10.1055/a-1952-2135
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with hepaticojejunostomy anastomotic strictures undergoing endoscopic and percutaneous treatment

Abstract: Background: Rising hepaticojejunostomy surgeries have led to an increase in benign strictures of the anastomosis. Double balloon enteroscopy assisted ERCP (DBE-ERCP) and percutaneous transhepatic biliary drainage (PTBD) are treatment options however there is lack of long-term outcomes, with no consensus on management. We performed a retrospective study assessing the outcomes of patients referred for endoscopic management of hepaticojejunostomy anastomotic strictures (HJAS). Methods: All consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the case of surgically altered anatomy, there are two access routes to a biliary lesion: percutaneous and endoscopic. In a recent study, Choi et al evaluated the outcomes of patients with HJS who underwent PTBD or DB-ERCP 8 . Among these patients, 82 underwent DB-ERCP for suspected HJS, in whom the endoscope could reach the desired site in 63 (technical success rate, 77%); and 41 patients were diagnosed with HJS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of surgically altered anatomy, there are two access routes to a biliary lesion: percutaneous and endoscopic. In a recent study, Choi et al evaluated the outcomes of patients with HJS who underwent PTBD or DB-ERCP 8 . Among these patients, 82 underwent DB-ERCP for suspected HJS, in whom the endoscope could reach the desired site in 63 (technical success rate, 77%); and 41 patients were diagnosed with HJS.…”
Section: Discussionmentioning
confidence: 99%
“…As HJS treatment techniques, balloon dilation, plastic stent, and metal stent deployment have been reported 2 8 9 10 11 15 16 17 18 19 22 23 24 . Although balloon dilation is a simple procedure with a high technical success rate, the restenosis rate has been reported to range from 34.3% to 52.2% 22 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-orthotopic liver transplantation (OLTx) BSs are a common complication that may occur in both preserved anatomies (stricture at the level of biliary anastomosis of the recipient and donor) and altered anatomies (stricture at the level of hepatic-jejunal anastomosis) and may require multiple endoscopic interventions (e.g., endoscopic multistenting) [ 91 ]. However, endoscopic multiple access in the case of an altered anatomy could be time consuming and challenging [ 92 ]. A recent retrospective study demonstrated the efficacy of PC for the treatment of post-OLTx BSs, with failure in only 2 out of 25 patients [ 93 ].…”
Section: Cholangioscopy Through Different Routesmentioning
confidence: 99%